Prevalence of Vibro Cholerae and Vibro Parahaemolyticus in Wild Birds, Rodents and Bats From Nanga Merit, Kapit - Evlyn Lemok, Noel (Universiti Malaysia Sarawak, UNIMAS, 2010)
Vibrio cholera and Vibrio parahaemolyticus are two common Vibrio species to cause illness to human. The common symptoms caused by these pathogens are vomiting, blood stool, fever, headache, and watery diarrhoel. In this project, the objectives were to isolate these two bacterial species from Nanga Merit samples and compare prevalence of these organisms in birds, rodents and bats. The Alkaline Peptone Water (APW) containing 1% NaCl was used to enriched the samples. CHROMagarTM Vibrio. CHROMagarTM Vibrio was used to isolate V. cholerae and V. parahaemolyticus. Thiosulphite Citrate Bile Salt (TCBS) agar was used to compare the colony growth and appearance from CHROMagarTM Vibrio. From thirty samples, only ten samples showed desired colony growth for V. parahaemolyticus and none for V. cholerae on CHROMagarTM Vibrio. These presumptive V. parahaemolyticus isolates undergone eight biochemical tests. However, none of the samples showed positive result for all biochemical tests. This study indicates a low risk of bacteria a being transmitted from the animal to the environment.